AKTIVITAS ANTIBAKTERI KOMBINASI EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.)DENGAN DAUN SIRSAK ( Annona muricata L.) TERHADAP Escherichia coli - Samsuar Samsuar; Yuli Wahyu Tri Mulyani; Brigitta Saniscara R.H (Program Studi Farmasi Universitas Tulang Bawang, 2022)
Infection is a type of disease that is often found in developing countries, including Indonesia. Escherichia coli is one of the most common causes of infection in society. The most common clinical symptoms in cases of this infection include watery diarrhea, abdominal cramps, low-grade fever, nausea, and malaise. Guava plants (Psidium guajava L.) and soursop plants (Annona muricata L.) are medicinal plants that are easy to find in Indonesia. Guava leaves and soursop leaves can be used as antibacterials. This study aims to determine the antibacterial activity of a combination of guava leaf extract (Psidium guajava L.) and soursop leaves (Annona muricata L.) against Escherichia coli bacteria. The method used is an experimental method of combining the concentrations of guava leaf extract and soursop leaves, namely K1 (100% + 0%), K2 (80% + 20%), K3 (60% + 40%), K4 (50% + 50% ), K5 (40%+60%), K6 (20%+80%), K7 (0%+100%), K(-) aquadest, K(+) Ciprofloxacin which was then followed by testing for Escherichia coli bacteria using the hole or well method. The variable measured in this study was the diameter of the inhibition zone formed in the combination of extracts. The results of observations were analyzed using One Way Annova with a sig value (0.000) <p value (0.050) followed by a follow-up tukey test which showed K1, K2, K3, K4, K5, K6, K7, K(-) and K(+) real different. It can be concluded from this study that the largest inhibition zone of combined extracts was found in K2 (80% guava leaf extract + 20% soursop leaf extract) with an average inhibition zone of 11.89 mm which belonged to the strong category. Inhibits the growth of E.coli bacteria. Keywords : guava leaves, soursop leaves, Escherichia coli, inhibition zone